Risks and Benefits with International Technology Transfer from Brazil to Angola - Vaisman, Rafael (Fronteira: Journal of Social, Technological and Environmental Science, 2013)
Thanks to the transfer of technology from Brazil, Angola is entering the sucroalcooleiro sector with multiple aims. These include creating jobs in rural areas, diversifying the energy mix and boosting exports. Angola is one of the countries that has envisioned international technology transfer as a strategy to increase participation in the global market, while decreasing its dependence on sugar imports. While the production of ethanol and sugar can bring about some benefits, technology transfer in this area is not without risks. It needs to be carefully crafted and executed, especially in accordance with the principles of sustainable development, which is by the government plan of Angola to include, rather than exclude, the rural poor. This study shows that stakeholders presented different opinions in relation to Biocom and sustainable development. The main reason is linked to the distinction between global, national and local levels. On the global level, ITT and Biocom are seen as alternative renewable sources of energy (ethanol) to fossil fuels, on the local level there is a concern with the socio-environmental issues which local communities might face, indeed ITT and Biocom are perceived as a risk in case locals lose their lands and do not receive compensation. On the national level, while there is the expectancy of employment, infrastructure development and attraction of investments in the country, there is a lack of trust in governance by Angolan civil society; which argues that Angolan government and enterprises do not encourage public participation nor allows it to happen. Technology transfer is perceived as a business and geopolitical strategy driven by private and state interests, undermining environmental and social costs. On the other hand technology transfer is seen as a key to foster economic opportunities towards sustainable development.